A computational study on the benefit of core-shell structured carbides to the erosion resistance of high-Cr cast irons. (November 2016) - Cui, Juan; Guo, Hong; Li, J.W.; Li, D.Y.; Parent, Leo; Tian, Harry
Abstract: Hard M7 C3 carbides in high Cr cast iron plays a crucial role in resisting wear. However, the hard carbides are less resistant to wear when impact force is involved, e.g., solid-particle erosion. Recent studies show that carbides may have a core (M7 C3 )-shell (M23 C6 ) structure, leading to elevated erosion resistance. In order to maximize the beneficial effect, we conducted this computational study to investigate how the carbide configuration, including shell thickness, carbide shape and orientation, affects the erosion resistance. FEM was employed to analyze the stress distribution in the vicinity of carbide/matrix interface, which is crucial to interfacial failure and thus the erosion resistance. The information obtained from this study would be beneficial to optimization of the core-shell structured carbides. Highlights: Core-shell structured carbides benefit the erosion resistance of cast irons. Modeling the influence of carbide configuration on the erosion resistance. FEM analysis of interfacial stress around the core-shell structured carbides.